Interactive Media Revolutionizes Education, Boosting Global Student Engagement: Media Interaktif Merevolusi Pendidikan, Meningkatkan Keterlibatan Siswa Secara Global - Seto, Armanda Bayu Rangga; Hasanah, Fitria Nur (Indonesian Journal of Innovation Studies, 2024)
This study focuses on developing desktop-based interactive learning media, "MISTAR," to address challenges such as student boredom and comprehension difficulties in computer lab settings. Using the ADDIE method, the research involved interviews with a network systems administration teacher, observations of X-grade TKJ students, and expert validation. Results showed high feasibility (88% media expert validation, 91% subject matter expert validation, and 90.8% average from limited-scale trials), indicating strong potential for improving engagement and understanding in educational environments. Further research is recommended to explore implementation and effectiveness in schools. Highlight: Improved Learning Experience: Interactive media development enhances student engagement effectively. Expert Validation: High feasibility validated by media and subject matter experts. Educational Impact: Interactive media improves understanding in computer lab environments. Keyword: Interactive Learning Media, ADDIE Method, Feasibility Evaluation, Engagement Improvement, Educational Research